The COVID-19 Pandemic and Chinese Trade Relations - Jaqueline Hansen; Antonia Kamaliev; Hans-Jörg Schmerer (Open Economies Review, 2023)
This paper presents an analysis of the effects of non-pharmaceutical interventions on countries' bilateral trade with China. Our panel regression results suggest a reduction in monthly Chinese exports to countries that introduced more stringent lockdown measures. We extend our analysis by decomposing observed trade flows into gravity and residual trade components. More stringent lockdowns are associated with less residual trade. Moreover, an event study approach reveals a negative effect of the Covid-19 outbreak in China but this effect vanishes after only 2 months.
Keywords: 330; Trade; China; Covid